In vitro model for DNA double‐strand break repair analysis in breast cancer reveals cell type–specific associations with age and prognosis. Issue 11 (5th August 2016) - Deniz, Miriam; Kaufmann, Julia; Stahl, Andreea; Gundelach, Theresa; Janni, Wolfgang; Hoffmann, Isabell; Keimling, Marlen; Hampp, Stephanie; Ihle, Michaela; Wiesmüller, Lisa
ABSTRACT: Dysfunction of homologous recombination is a common denominator of changes associated with breast cancer–predisposing mutations. In our previous work, we identified a functional signature in peripheral blood lymphocytes from women who were predisposed that indicated a shift from homologous recombination to alternative, error‐prone DNA double‐strand break (DSB) repair pathways. To capture both hereditary and nonhereditary factors, we newly established a protocol for isolation and ex vivo analysis of epithelial cells, epithelialmesenchymal transition cells (EMTs), and fibroblasts from breast cancer specimens (147 patients). By applying a fluorescence‐based test system, we analyzed the error‐prone DSB repair pathway microhomology‐mediated end joininginthese tumor‐derivedcell types and peripheral blood lymphocytes. Inparallel, we investigated DNA lesion processing by quantitative immunofluorescence microscopy of histone H2AX phosphorylated on Ser139 focus after radiomimetic treatment. Our study reveals elevated histone H2AX phosphorylated on Ser139 damage removal in epithelial cells, not EMTs, and poly(ADP‐ribose)polymerase inhibitor sensitivities, which suggested a DSB repair pathway shift with increasing patient age. Of interest, we found elevated microhomology‐mediated end joining in EMTs, not epithelial cells, from patients who received a treatment recommendation of adjuvant chemotherapy, that is, those with high‐risk tumors. Our discoveries of altered DSB repair activities in cells may serve as a method to further classify breast cancer to predict responsiveness to adjuvant chemotherapy and/or therapeutics that target DSB repair‐dysfunctional tumors.—Deniz, M., Kaufmann, J., Stahl, A., Gundelach, T., Janni, W., Hoffmann, I., Keimling, M., Hampp, S., Ihle, M., Wiesmüller, L. In vitro model for DNA double‐strand break repair analysis in breast cancer reveals cell type–specific associations with age and prognosis. FASEB J. 30, 3786–3799 (2016) www.fasebj.org